2020
DOI: 10.3390/biomedicines8080257
|View full text |Cite
|
Sign up to set email alerts
|

The First Human Clinical Trial on the Skin Depigmentation Efficacy of Glycinamide Hydrochloride

Abstract: A previous study identified certain low molecular anti-melanogenic peptides that share a common sequence with α-melanocyte stimulating hormone (MSH) and end with a glycinamide moiety. Glycinamide itself also showed anti-melanogenic activity in cell-based assays, but neither glycine nor acetyl glycinamide were active, which indicated a special structure and activity relationship. The aim of this study was to examine the skin depigmentation efficacy of glycinamide hydrochloride in human subjects. The primary ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…A variety of peptides and amino acid analogs were described to modulate melanin synthesis in cells, although their therapeutic utility remains to be further verified. In vivo and clinical results have been provided for MC1R targeting molecules, such as [Nle 4 -D -Phe 7 ]-α-MSH [71,72], and glycinamide hydrochloride [126], and an inhibitor of melanin synthetic reaction, such as oxidized glutathione [95]. These studies suggest that certain amino acids, peptides, and their analogs may be a promising drug candidate for up-and downregulating skin pigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of peptides and amino acid analogs were described to modulate melanin synthesis in cells, although their therapeutic utility remains to be further verified. In vivo and clinical results have been provided for MC1R targeting molecules, such as [Nle 4 -D -Phe 7 ]-α-MSH [71,72], and glycinamide hydrochloride [126], and an inhibitor of melanin synthetic reaction, such as oxidized glutathione [95]. These studies suggest that certain amino acids, peptides, and their analogs may be a promising drug candidate for up-and downregulating skin pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin increasing molecules can be used to alleviate photosensitive skin, to prevent photocarcinogenesis, and to treat vitiligo vulgaris [15,71,72]. Conversely, melanin decreasing molecules can be used to treat various types of hyperpigmentation for medical and aesthetic purposes [58,59,95,126].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Follow-up work in a human clinical trial reported that application of glycinamide to facial skin decreased melanin index and skin pigmentation while increasing skin lightness, as compared to a control formulation lacking glycinamide. 51 These data suggest that an in vitro functional antagonist mixture-based positional scan can successfully identify clinically relevant compounds.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Further truncation studies led to the observation that the C-terminal amino acid in these tetrapeptides, glycinamide (H-G-NH 2 ), possessed anti-melanogenic activity at 30 and 100 μM concentrations . Follow-up work in a human clinical trial reported that application of glycinamide to facial skin decreased melanin index and skin pigmentation while increasing skin lightness, as compared to a control formulation lacking glycinamide . These data suggest that an in vitro functional antagonist mixture-based positional scan can successfully identify clinically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%